NAVIGATING DATA PRIVACY AND CYBERSECURITY CHALLENGES IN HEALTH INFORMATION TECHNOLOGY - Dheeraj Narayanan, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The rapid adoption of Health Information Technology (HIT) has significantly transformed healthcare by improving efficiency, accuracy, and accessibility in patient care. However, this digital shift has also introduced substantial data privacy and cybersecurity challenges. This paper explores the key threats to HIT, including ransomware, phishing, and insider breaches, and discusses the regulatory frameworks, such as HIPAA and GDPR, that aim to protect patient data. It also examines the critical strategies, such as encryption, access control, and AI-driven solutions, to enhance cybersecurity while addressing the financial, operational, and interoperability challenges healthcare organizations face. The findings underscore the importance of balancing security with usability and the need for continued investment in innovative technologies to safeguard sensitive healthcare information.